Science in today's world for senior high school : empowerment technologies - Callo, ErwinReyes (Quezon City : Sibs Publishing House, Inc., 2018)
"This textbook will help you go over the ICT concepts that are prerequisite for the skills needed in the world of work." Each chapter focuses on a Key Understanding along with the Key Questions as your guide in going through the important sub-topics. Pre-learning Check will help you review basic skills while the side bars contain a Glimpse of History in the field of ICT. Quick Quiz and Quick Lab will enable you to take concepts on an easier note while applying skills on the spot. This also includes featured technology and careers in ICT. Assessments vary from Simple objective tests to checking insights as well as performance tasks that will test how you apply the concepts and skills in real life."
Includes references.
English text.
Keywords: Information technology; Computer networks